Economic Development as a Social Process of Multiple Space-Time Scales - Soares Bandeira de Mello Filho, Marcelo (Organizações & Sociedade, 2023)
The article seeks, first, to demonstrate how the concept of development has been used in different ways throughout history. The classical developmentalist authors understood the phenomenon as a complex process, which involved structural changes, sectoral economic transformations, political projects of social change and action and planning by various economic and political actors. Developmentalist ideas influenced sophisticated processes of social transformation that took place especially during the “golden age” of capitalism. From the 1980s onwards, reductionist theories about development have gained momentum. They seek to explain development as the result, for example, of productive specialization, entrepreneurial action or local economic arrangements. The article also aims to establish methodological parameters for the rejection of reductionist approaches to development and for the defence of comprehensive theories, which understand it as a complex social phenomenon that occurs in multiple space-time scales.